PSYCHIATRIC INTERVIEW OF PATIENTS WITH CANCER - Yu. N. Zubkova; I. A. Kurmukov; O. A. Obukhova; Sh. R. Kashia (Сибирский онкологический журнал, 2019)
Background. Psychiatrists providing consultation in cancer centers need to understand the patient’s mental health without possibility of collecting data on the objective case history and follow-up.Purpose: to analyze the modern methods of assessment of psychopathological disorders in cancer patients.Material and Methods. Publications indexed in PubMed and devoted to the analysis of defense mechanisms, strategies for overcoming challenges, responses to acute and chronic stress, and support for family members of cancer patients were analyzed.Results. Modified psychosomatic interviews used for cancer patients, attachment styles, coping strategies, and defense mechanisms were described. The taxonomic system of the most common mental disorders in modern psycho-oncology was presented.Conclusion. The modified psychiatric interview, during which the defense mechanisms, coping styles, coping reactions with acute and chronic stress, methods of functioning of cancer patient’s family are assessed, allows a psychiatrist to obtain essential information about psychopathological status of a patient within the first (and often the only) appointment. A multidimensional diagnostic approach helps to assess the involvement of various damaging factors in a patient’s current mental status. Conclusion made by a psychiatrist in terms of the taxonomic systems of the International Statistical Classification of Diseases and Health Related Problems (ICD) or the Diagnostic and Statistical Manual of Mental Disorders (DSM) allows him to provide information to an oncologist in a uniquely interpretable (standardized) form.